2022
DOI: 10.5114/ait.2022.114251
|View full text |Cite
|
Sign up to set email alerts
|

General versus regional anaesthesia for hip fracture surgery – impact on mortality and length of stay

Abstract: Hip fractures are considered a public epidemic health problem worldwide [1]. It is an extremely common orthopaedic condition with a projection of increase that could range between 7.3 and 21.3 million cases by 2050 [2]. This kind of fracture is more frequent among elderly people and, despite the improvement in medical instruments, surgical and anaesthetic techniques, it is still associated with high morbidity and mortality [3].Both regional and general anaesthesia are valid options for hip fractures surgery, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In a recent study published in 2022, the authors concluded that spinal and general anesthesia both achieve similar outcomes for patients undergoing hip fracture surgery and they observed no differences in mortality between the two anesthetic groups [ 41 ]. In another recent study, Ana et al [ 42 ] identified 562 patients who had hip fracture surgery, 361 of whom were given general anesthesia and 201 of whom were given regional anesthesia. There was no statistically significant difference in the risk of perioperative and 30-day mortality in the adjusted analysis.…”
Section: Bone Cement Implantation Syndromementioning
confidence: 99%
“…In a recent study published in 2022, the authors concluded that spinal and general anesthesia both achieve similar outcomes for patients undergoing hip fracture surgery and they observed no differences in mortality between the two anesthetic groups [ 41 ]. In another recent study, Ana et al [ 42 ] identified 562 patients who had hip fracture surgery, 361 of whom were given general anesthesia and 201 of whom were given regional anesthesia. There was no statistically significant difference in the risk of perioperative and 30-day mortality in the adjusted analysis.…”
Section: Bone Cement Implantation Syndromementioning
confidence: 99%